Rare disorders can be an underlying cause of cyclic vomiting: Familial Mediterranean fever, Helicobacter pylori gastritis, and cavernous transformation of the portal vein - Egritaş Gürkan, Ödül; Ünlüsoy Aksu, Aysel; Demirtaş, Zeliha; Dalgıç, Buket (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Considering the etiology of cyclic vomiting syndrome (CVS) in childhood, a variety of underlying organic causes has been clearly identified in the literature. The aim of this study was to emphasize that endoscopic evaluation in the first step may help diagnosis and treatment in patients with CVS, unlike the CVS-related “North American Society for Pediatric Gastroenterology, Hepatology and Nutrition” (NASPGHAN) consensus statement in 2008. Materials and Methods: The medical files of patients with vomiting complaints admitted to our tertiary center between the years 2007 and 2012 were analyzed retrospectively. Patients were identified according to the International Classification of Diseases (ICD) codes at their initial presentation, including vomiting. Results: A total of 815 patients with vomiting complaints were evaluated. Of the 379 patients who presented with vomiting only, 336 patients were already being followed for chronic vomiting. Cyclic vomiting was detected in 31 out of 336 patients. Conclusion: In our series, familial Mediterranean fever (FMF), cavernous transformation of the portal vein, and Helicobacter pylori (HP) gastritis presented with CVS for the first time in the pediatric age group. We emphasize that endoscopic evaluation in patients with CVS should be performed as the first step for appropriate diagnosis and treatment.